PENGARUH LAMA PERENDAMAN DALAM LARUTAN Ca(OH)2 JENUH TERHADAP KANDUNGAN GIZI DAN KARAKTERISTIK SENSORIS JAMUR TIRAM CRISPY - Fuadi, Ferino; Wisaniyasa, Ni Wayan; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2016)
This study aims to determine the effect of the length of soaking time in  Ca(OH) 2 saturated solution on the nutrient content and sensory characteristics of crispy oyster mushrooms and determine the length of time of soaking in a saturated solution of Ca(OH) 2 right to produce a crispy oyster mushroom with best characteristics. The experimental design used was Completely Random Design (CRD) with treatment duration of soaking that consists of 5 levels: T0= without soaking, T1= 15 minutes, T2= 30 minutes, T3= 45 minutes, T4= 60 minutes. Each treatment was repeated three times to obtain 15 experimental units. The results showed that treatment duration of soaking in a saturated solution of Ca(OH) 2 affect the ash content, protein content, fat content, crude fiber content, colour, texture and overall acceptance, but has no effect on the moisture content, carbohydrate content, taste, and aroma. Characteristics of the best crispy oyster mushroom soaking time was obtained in the treatment of saturated solution Ca(OH) 2 15 minutes with 26.82% moisture, 0.68% ash content, 6.73% protein, 2.32% fat, 63.18 carbohydrate, 9.45% crude fiber content with sensory evaluation that consists of color with score test 4,75 (rather tawny) and hedonic test 5.15 (rather like), aroma 5.13 (rather like), taste 5.25 (rather liked), texture with score test 3,50 (normal) and hedonic test 3.75 (normal) and 5.00 over all acceptance (rather like).
Keywords: soaking, saturated solution of Ca(OH)2, crispy oyster mushrooms